Titanium Phosphonate Based Metal–Organic Frameworks with Hierarchical Porosity for Enhanced Photocatalytic Hydrogen Evolution - Li, Hui; Sun, Ying; Yuan, Zhong‐Yong; Zhu, Yun‐Pei; Ma, Tian‐Yi (Angewandte Chemie International Edition, 2018)
Photocatalytic hydrogen production is crucial for solar‐to‐chemical conversion process, wherein high‐efficiency photocatalysts lie in the heart of this area. A photocatalyst of hierarchically mesoporous titanium phosphonate based metal–organic frameworks, featuring well‐structured spheres, a periodic mesostructure, and large secondary mesoporosity, are rationally designed with the complex of polyelectrolyte and cathodic surfactant serving as the template. The well‐structured hierarchical porosity and homogeneously incorporated phosphonate groups can favor the mass transfer and strong optical absorption during the photocatalytic reactions. Correspondingly, the titanium phosphonates exhibit significantly improved photocatalytic hydrogen evolution rate along with impressive stability. This work can provide more insights into designing advanced photocatalysts for energy conversion and render a tunable platform in photoelectrochemistry. A multi‐structured photocatalyst: A metal–organic framework (MOF) nanostructure synthesized by a surfactant‐directed strategy features a stable framework of titanium phosphates, a well‐defined sphere, and hierarchical nanopores. These features ensure competitive photoactivity in evolving hydrogen under both visible light and full‐spectrum simulator irradiation, along with high durability.